First record of Leporacarus gibbus infestation in domestic rabbits (Oryctolagus cuniculus) in southern Rio Grande do Sul state, Brazil - Soares Martins, Natália; Somavilla Lignon, Júlia; Moscarelli Pinto, Diego; Roberto Alves Ferreira, Marcos; Gasparetto, Raíssa; Geraldo Pappen, Felipe (Acta veterinaria Brasílica, 2024)
Leporacarus gibbus is an ectoparasite of rabbits, in which infestation is usually subclinical and can, sometimes, be underdiagnosed. This case report presents a symptomatic infestation by L. gibbus in rabbits, for the first time, at southern Rio Grande do Sul, Brazil. Forty-four rabbits from a vivarium in the city of Capão do Leão, Rio Grande do Sul State, Brazil, were evaluated. Dermatitis and alopecia were observed on the hind legs, neck, and back of the animals. External inspection revealed the presence of ectoparasites. Skin scraping, adhesive tape impression, and hair plucking were performed for diagnosis. However, only after stereomicroscopic examination of the coat, the presence of mites was revealed. The specimens were clarified in phenol/xylene and mounted in a non-permanent preparation. After light microscopic evaluation, the specimens were taxonomically classified as L. gibbus. Ivermectin treatment was applied, with 100% efficacy after 7 days. This report describes, for the first time, a case of L. gibbus infestation in domestic rabbits in the region, with dermatological manifestation.